Morphine Pharmacodynamics in Mechanically Ventilated Preterm Neonates Undergoing Endotracheal Suctioning. (21st January 2017) - Välitalo, PA; Krekels, EHJ; van Dijk, M; Simons, SHP; Tibboel, D; Knibbe, CAJ
Abstract : To date, morphine pharmacokinetics (PKs) are well quantified in neonates, but results about its efficacy are ambiguous. This work presents an analysis of a previously published study on pain measurements in mechanically ventilated preterm neonates who received either morphine or placebo to improve comfort during invasive ventilation. The research question was whether morphine reduces the pain associated with endotracheal or nasal suctioning before, during, and after suctioning. Because these neonates cannot verbalize their pain levels, pain was assessed on the basis of several validated pain measurement instruments (i.e., COMFORT‐B, preterm infant pain profile [PIPP], Neonatal Infant Pain Scale (NIPS), and visual analogue scale (VAS)). The item response theory (IRT) was used to analyze the data in order for us to handle the data from multiple‐item pain scores. The analysis showed an intra‐individual relationship between morphine concentrations and pain reduction, as measured by COMFORT‐B and VAS. However, the small magnitude of the morphine effect was not considered clinically relevant for this intervention in preterm neonates.